La vidriera de Nuestra Señora del Pilar, el ‘honor de nuestro pueblo’: The Stained-glass Window of Our Lady of Pilar, the ‘Honor of Our people’ - Mur Royo, Javier (Studium, 2020)
Proyectada en 1908 y colocada en 1914, la vidriera de Nuestra Señora del Pilar fue una de las primeras vidrieras artísticas fabricadas por La Veneciana. Pese a ocupar el mayor ventanal de la catedral-basílica de Zaragoza permanece ignorada por las guías turísticas e Internet. Este trabajo arroja luz sobre dicho vitral, su diseñador y el arte sobre cristal. Analizamos su composición pilarista en el contexto de la historia civil, religiosa y legendaria de Zaragoza. Concluiremos con el profundo significado simbólico de esta vidriera que consagra a la Virgen del Pilar como el honor del pueblo zaragozano, aragonés y español así como un elemento del espíritu de la reconciliación hispano-francesa de 1908.Palabras clave: vidriera artística, El Pilar, Zaragoza, La Veneciana, Guyonnet, relaciones hispano-francesas.AbstractProjected in 1908 and placed in 1914, the stained-glass window of Nuestra Señora del Pilar was one of the first artistic stained-glass windows manufactured by La Veneciana. Despite occupying the largest window of the cathedral-basilica of Zaragoza remains ignored by tourist guides and the Internet. This work sheds light on this stained-glass window, your designer and art on glass. Next, we will analyze its ‘pilarista’ composition, a synthesis of the civil, religious and legendary history of Zaragoza. We will conclude with the deep symbolic meaning of this stained-glass window, which consecrates the Virgen del Pilar as the honor of the people of Zaragoza, Aragon and Spain. Eventually, this article constitutes an invitation to consider this work as an element of the spirit of Spanish-French reconciliation of 1908.Key words: stained-glass, El Pilar, Zaragoza, La Veneciana, Guyonnet, Spanish-French relations.
Keywords: stained-glass; El Pilar; Zaragoza; La Veneciana; Guyonnet; Spanish-French relations; vidriera artística; relaciones hispano-francesas